Fagus sylvatica C4 Trituration Proving and Clinical Applications - Renoux, Hélène (Homœopathic Links, 2021)
Fagus sylvatica, the beech, has long been linked to European history, along with the oak. This homeopathic trituration proving reports on the main pathogenetic themes which led to successful prescriptions. Stiffness of the shoulders, alternating symptoms and love for forests appear to be key symptoms. More study of this remedy, and more prescriptions would be necessary to explore widely the many possibilities of this homeopathic medicine.
Keywords: homeopathic trituration proving; Fagus sylvatica; trapezius stiffness; love for forests